Electrocardiographic Changes and Arrhythmia in Fabry Disease - Namdar, Mehdi (Frontiers in Cardiovascular Medicine, 2016)
Fabry disease is an X-chromosome-linked lysosomal storage disease characterized by a deficient activity or, in most males, absence of the enzyme alpha-galactosidase A (a-Gal A) leading to systemic, primary lysosomal accumulation of globotriaosylceramide (Gb3). Multi-system morbidity commonly develops in childhood and, with progression of the disease, life-threatening complications often occur in adulthood including renal failure, cardiovascular dysfunction, neuropathy and stroke. Life expectancy is reduced by an average of 15 years in female patients and 20 years in males. The pathognomonic Gb3 accumulation has been repeatedly observed over the past decades by many groups in vascular endothelial and smooth muscle cells, cardiomyocytes, cardiac conduction tissue and valvular fibroblasts. Although incompletely described, it is likely that inflammatory and neuro-hormonal mechanisms are involved in subsequent cellular and vascular dysfunction, leading to tissue ischaemia, hypertrophy, and fibrosis.